ANALYSIS OF THE DATA OF MICROWAVE RADIOMETRY AND THE HYPOTHESIS ON THERMOASYMMETRY - A. G. Losev; E. A. Mazepa; H. M. Suleymanova (Современная наука и инновации, 2022)
One of the urgent tasks facing medicine, mathematics, computer science and information technology is the development and implementation of effective decision support systems. Such systems, using the methods and algorithms of machine learning, should help specialists in the problems of diagnosis, disease prognosis, etc.